INDUCTION AND RECOVERY TIMES IN THREE SIZES OF Clarias gariepinus EXPOSED TO ANAESTHETIC TRICAINE METHANESULFONATE (MS-222) - AKINROTIMI, O.A; GABRIEL, U.U.; ERONDU, E.S. (Nigerian Journal of Fisheries, 2012)
The efficacy of tricaine methanesulfonate (MS 222) in three sizes of African catfish (Clarias gariepinus) was investigated. Three sizes: fingerlings (mean length 12. 14 cm  3.62 SD; mean weight 18.62 g  1.68 SD); juveniles (mean length 25:68 cm  3.14 SD, mean weight 354.64 g  11.24 SD) and adult (mean length 51.68 cm  11.81 SD; mean weight 1102.41 g  40.68 SD), were exposed by immersion to different concentrations: 0.00 ml/l (control) 50.00, 100.00, 150.00 and 200.00 ml/l of MS 222 solution. The induction time (time taken for the fish to get anaesthetized) reduced significantly (P < 0.05), with increasing concentrations of the anaesthetics, while the recovery time (time taken for the fish to resume active swimming) increased considerably as the concentrations of MS-222 increased. The induction, recovery time, and survival of C. gariepinus to the anaesthetics were higher in adult size compared to fingerlings and juveniles. Hence MS-222 can be used to sedate all sizes of this fish species with optimum dosage at 50 ml/l for fingerlings and juveniles and 150.0 ml/l for adults.